Pengelolaan Sumberdaya Alam di Kabupaten Kapuas - Yula Yunara; Siana Siana; Meta Melinda Aldis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze and evaluate natural resource management in Kapuas Regency, as well as identify potential improvements in efforts to maintain environmental sustainability and empower local communities. Kapuas Regency, which is located in Central Kalimantan Province, Indonesia, has great natural resource potential, such as forests, rivers and biodiversity. However, less than sustainable management can threaten ecosystem sustainability and community welfare. This research uses secondary data analysis methods, interviews and field surveys to collect data related to natural resource management in Kapuas Regency. The research results show that there are many challenges faced in maintaining the sustainability of natural resources, including illegal logging, changes in land use, and conflicts over natural resources. In addition, inadequate management can also have a negative impact on the livelihoods of local communities. In order to achieve sustainability, this research recommends various strategic steps, including increasing supervision and law enforcement against illegal logging activities, developing forest restoration programs, promoting sustainable agriculture, and community empowerment through education and training. In addition, collaboration between government, NGOs and local communities is considered important to create sustainable solutions in natural resource management.